Histopathological findings in systemic sclerosis-related myopathy: fibrosis and microangiopathy with lack of cellular inflammation. (January 2017) - Corallo, Claudio; Cutolo, Maurizio; Volpi, Nila; Franci, Daniela; Aglianò, Margherita; Montella, Antonio; Chirico, Chiara; Gonnelli, Stefano; Nuti, Ranuccio; Giordano, Nicola
Objectives: The objective of this study was to identify specific histopathological features of skeletal muscle involvement in systemic sclerosis (SSc) patients. Methods: A total of 35 out of 112 SSc-patients (32%, including 81% female and 68% diffuse scleroderma) presenting clinical, biological and electromyographic (EMG) features of muscle weakness, were included. Patients underwent vastus lateralis biopsy, assessed for individual pathologic features including fibrosis [type I collagen (Coll-I), transforming growth factor β (TGF-β)], microangiopathy [cluster of differentiation 31 (CD31), pro-angiogenic vascular endothelial growth factor A (VEGF-A), anti-angiogenic VEGF-A165b], immune/ inflammatory response [CD4, CD8, CD20, human leucocyte antigens ABC (HLA-ABC)], and membranolytic attack complex (MAC). SSc biopsies were compared with biopsies of ( n = 35) idiopathic inflammatory myopathies (IIMs) and to ( n = 35) noninflammatory myopathies (NIMs). Ultrastructural abnormalities of SSc myopathy were also analyzed by transmission electron microscopy (TEM). Results: Fibrosis in SSc myopathy (81%) is higher compared with IIM (32%, p < 0.05) and with NIM (18%, p < 0.05). Vascular involvement is dominant in SSc muscle (92%), and in IIM (78%) compared with NIM (21%, p < 0.05). In particular, CD31 shows loss of endomysial vessels in SSc myopathy compared with IIM ( p < 0.05) and with NIM ( p < 0.01). VEGF-A is downregulated in SSc myopathy compared with IIM ( p < 0.05) and NIM ( p < 0.05). Conversely, VEGF-A165b is upregulated in SSc myopathy. The SSc immune/inflammatory response suggested humoral process with majority (85%) HLA-ABC fibral neoexpression and complement deposits on endomysial capillaries MAC, compared with IIM ( p < 0.05), characterized by CD4 + /CD8 + /B-cell infiltrate, and NIM ( p < 0.05). TEM analysis showed SSc vascular alterations consisting of thickening and lamination of basement membrane and endothelial cell 'swelling' coupled to endomysial/perimysial fibrosis. Conclusions: Fibrosis, microangiopathy and humoral immunity are predominant in SSc myopathy, even if it is difficult to identify specific histopathological hallmarks of muscle involvement in SSc, since they could be present also in other (IIM/NIM) myopathies.